2020
DOI: 10.30884/jogs/2020.02.11
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and Life Satisfaction of the Polish Population. Before and during the COVID-19 Pandemic

Abstract: The main objective of the present research was to examine whether the attitude towards globalization and life satisfaction during the COVID-19 pandemic differs from the one observed beforehand. An additional goal was to find out whether the attitude to globalization during the pandemic can serve as a predictor of life satisfaction. On the basis of data obtained by Folk Theory of Social Change, we assume that the attitudes towards globalization and their correlation with life satisfaction are shaped by personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Results from pre-pandemic studies have shown no correlation between attitudes towards globalization and life satisfaction (Jasiński et al, 2019). The results of research conducted during the first wave of the pandemic in Poland indicate that the context of the pandemic, understood as a manifestation of globalization, clearly strengthens the correlation between fearful attitude towards globalization and life satisfaction (Jasiński, Bąkowska, 2020). The data presented here, collected during the second and third waves of COVID-19, indicate that in both emerging adults and seniors the higher the sense of overall quality of life, the lower the intensity of fearful attitude towards globalization.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Results from pre-pandemic studies have shown no correlation between attitudes towards globalization and life satisfaction (Jasiński et al, 2019). The results of research conducted during the first wave of the pandemic in Poland indicate that the context of the pandemic, understood as a manifestation of globalization, clearly strengthens the correlation between fearful attitude towards globalization and life satisfaction (Jasiński, Bąkowska, 2020). The data presented here, collected during the second and third waves of COVID-19, indicate that in both emerging adults and seniors the higher the sense of overall quality of life, the lower the intensity of fearful attitude towards globalization.…”
Section: Discussionmentioning
confidence: 98%
“…A fearful attitude is characterized by sensitivity to the possible dangers of globalization and a lack of confidence in the changes experienced in the modern world. Previous research has confirmed that the pandemic decreased the level of acceptance towards globalization and increased the strength of the negative correlation between fearful attitude towards globalization and life satisfaction (Jasiński, Bąkowska, 2020). However, the problem of determinants of attitudes towards globalization needs further study.…”
Section: Introductionmentioning
confidence: 97%
“…2014, 2016b;Grinin L., Grinin A., and Korotayev 2017a), the sixth K-wave will not be frequently mentioned here. There are a huge number of articles about COVID-19 pandemic (caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its effect on society (e.g., Atkeson 2020;Baker et al 2020;Grinin 2020;Irshad 2020;Jasiński and Bąkowska 2020; see also further references below). In addition to research on possible strategies for dealing with the pandemic (including its consequences) and various medical aspects, many other issues are being studied, from economic consequences to the impact on the climate (Aslam et al 2020;Belhadi et al 2020;Brammer et al 2020;Chakraborty and Maity 2020;Forster et al 2020;Yoo and Managi 2020).…”
Section: Introduction Multidimensional Impact Of Covid-19mentioning
confidence: 99%